2021
DOI: 10.3390/ijerph18105394
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns and Functioning. A Contextual–Functional Approach to Pain Catastrophizing in Women with Fibromyalgia

Abstract: Background: The psychological flexibility model states that activity patterns are not deemed to be intrinsically functional or dysfunctional; it is considered that underlying factors, such as personal goals and contextual factors, are what will determine their effects on disability. Pain catastrophizing has frequently been associated with several important pain-related outcomes. Despite its recent conceptualization within affective–motivational approaches, its moderating role between activity patterns and dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…There was also no direct effect of walking on mental fatigue. Although there are a number of professionals who recommend physical therapy as a strategy to alleviate mental fatigue [ 45 ], the results obtained here indicate that in patients with fibromyalgia, walking without having certain cognitive abilities has no effect on mental fatigue. This could mean that for these women to be able to perceive walking as beneficial for mental clearing, they need to possess various cognitive processing skills (i.e., cognitive defusion and acceptance of chronic pain), and that it is not enough to manage a single cognitive ability or none at all.…”
Section: Discussionmentioning
confidence: 63%
“…There was also no direct effect of walking on mental fatigue. Although there are a number of professionals who recommend physical therapy as a strategy to alleviate mental fatigue [ 45 ], the results obtained here indicate that in patients with fibromyalgia, walking without having certain cognitive abilities has no effect on mental fatigue. This could mean that for these women to be able to perceive walking as beneficial for mental clearing, they need to possess various cognitive processing skills (i.e., cognitive defusion and acceptance of chronic pain), and that it is not enough to manage a single cognitive ability or none at all.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, Lukkahatai et al [ 28 ] revealed that fatigue was associated with several symptoms and psychological factors, including pain catastrophism. Our results suggest that the discrepancy in findings might be because catastrophism has been studied in a global and homogenous manner, and its different components have not been analyzed separately [ 24 , 25 , 54 ]. In fact, our findings show no significant results for catastrophism as a general construct but did find differential results when each dimension is studied separately.…”
Section: Discussionmentioning
confidence: 92%
“…The results are discussed in the context of the psychological flexibility model and personalized interventions. Furthermore, the fact that these results were not found in relation to helplessness shows how complex catastrophism truly is [ 52 ] and the possibility that the different components involved do not have the same role [ 25 , 52 , 53 , 54 ] as has been suggested in recent studies [ 24 ]. Therefore, it is important that future studies focus on catastrophism take into account specifically all its components, not in a general manner, as has been done in most studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations